Impact of Corporate Governance on Performance of Public Commercial Banks in Nepal - Hada, Maheshwar Lal (Journal of Economics and Management, 2024)
With regard to non-performing loans in Nepal, this research study seeks to investigate the effect of corporate governance on the profitability of public commercial banks. While several studies have examined the "Impact of Corporate Governance on profitability of commercial banks in Nepal," publicly traded commercial banks in the country have been the subject of far less investigation. By focusing just on Nepal's banking sector, this research aimed to address that void. The non-performing loan (NPL) is used as a dependent variable to measure performance, while the percentage of female directors, audit committee size, audit committee independence, board diligence, and board size all serve as independent variables in corporate governance. The study examined the governance procedures and their influence on the performance of public commercial banks in Nepal using panel data analysis. The data was collected from 2017/018 to 2021/022, and statistical methods such as descriptive statistics, correlation, multiple regression, and t-test were employed. Board diligence (DB) significantly and positively affects nonperforming loans (NPL), according to the empirical findings. Other factors (BS, FD AC, BI, ACI) did not significantly affect the return on assets (ROA) of Nepal's public commercial banks, according to the results.